Microvascular Obstruction In PCI - A Review - Haque, Fazlul; Momenuzzaman, Nam; Begum, Fatema; Khan, Kaiser Nasrullah; Sohail, KM; Adhikary, Dipal Krisno; Shafique, AM; Ulamin, Mahbub; Milius, Zahiruddin; Rahman, Razur; et al. (University Heart Journal, 2012)
DOI: http://dx.doi.org/10.3329/uhj.v7i1.10211 UHJ 2011; 7(1): 48-52